Thermal analysis of a feedwater heater tubesheet through coupling of a 1D network solver and CFD - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2021)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2019.